Reinstating memories’ temporal context at encoding causes Sisyphus-like memory rejuvenation - Karl-Heinz T. Bäuml; Sarah R. Meixensperger; Marilena L. Hirsch (Proceedings of the National Academy of Sciences, 2025)
As memories age, their immediate retrievability decreases albeit, due to ongoing memory consolidation, their future rate of forgetting weakens. Here, we show in two experiments ( N = 1.216 participants) that mentally traveling back in time to older memories’ temporal context at encoding reverses the two effects and makes the memories similar again to how they were at an earlier point in time. Mental time travel increased both the memories’ immediate retrievability and their future rate of forgetting when individuals attempted to reinstate context deliberately and actively and when they retrieved other memories sharing a similar temporal context. Intriguingly, the forgetting after mental time travel even followed the same trajectory as the forgetting after encoding. Attempts to reinstate memories’ encoding context thus rejuvenated memories, although the degree of rejuvenation decreased as temporal lag between encoding and the reinstatement attempts increased, which was mediated by the fact that, with increasing lag, decreasing proportions of the encoded memories were reactivated and reconsolidated in response to participants’ reinstatement attempts. Mentally traveling back in time creates rejuvenation cycles with enhanced retrievability followed by a restart of forgetting and consolidation processes. Recurring rejuvenation cycles may thus be key to maintain memories’ retrievability over longer periods of time, painting the picture of Sisyphus-like memory resurrection.